Neonatal and Pregnancy Outcome in Primary Antiphospholipid Syndrome: A 10-year Experience in One Medical Center - An-Kuo Chou; Song-Chou Hsieh; Yi-Ning Su; Suh-Fang Jeng; Chien-Yi Chen; Hung-Chieh Chou; Po-Nien Tsao; Wu-Shiun Hsieh (Elsevier, 2009)
Antiphospholipid syndrome (APS) in pregnancy is characterized by the presence of maternal autoantibodies in association with recurrent fetal loss and severe obstetric complications such as prematurity, intrauterine growth retardation, or placental insufficiency. This study aimed to assess the perinatal outcomes in neonates born to mothers with APS. Methods: The medical records of pregnant women with APS and their offspring were retrospectively collected between January 1997 and July 2007. Maternal and perinatal histories including demographic data, medications, obstetric histories, and neonatal clinical manifestations and laboratory data were analyzed. Results: Eleven women with a diagnosis of primary APS were included. Eight of these patients had experienced frequent spontaneous abortions (72.7%), and four had unexplained fetal deaths (36.3%). None of them had vascular thrombosis. Specific autoimmune antibodies were detected, including anticardiolipin antibody (n = 6), anti-β2 glycoprotein I (n = 3), and antiphospholipid antibody (n = 7). Among the pregnancies, five had preterm births (45.4%), two had intrauterine growth retardation (18.1%), and one had intrauterine fetal demise (9.1%). Thrombocytopenia was noted in three babies, all of whose mothers had lower platelet counts. One patient with neonatal thrombocytopenia developed intracranial hemorrhage, seen on brain images. Conclusions: This limited study suggests that neonates born to mothers with primary APS are at risk of prematurity, being small for gestational age, and having thrombocytopenia. Further large, prospective studies are required to better define the perinatal outcomes.